GeTFEP: A general transfer free energy profile of transmembrane proteins. (11th November 2019) - Tian, Wei; Naveed, Hammad; Lin, Meishan; Liang, Jie
Abstract: Free energy of transferring amino acid side‐chains from aqueous environment into lipid bilayers, known as transfer free energy (TFE), provides important information on the thermodynamic stability of membrane proteins. In this study, we derived a TFE profile named General Transfer Free Energy Profile (GeTFEP) based on computation of the TFEs of 58 β ‐barrel membrane proteins ( β MPs). The GeTFEP agrees well with experimentally measured and computationally derived TFEs. Analysis based on the GeTFEP shows that residues in different regions of the transmembrane (TM) segments of β MPs have different roles during the membrane insertion process. Results further reveal the importance of the sequence pattern of TM strands in stabilizing β MPs in the membrane environment. In addition, we show that GeTFEP can be used to predict the positioning and the orientation of β MPs in the membrane. We also show that GeTFEP can be used to identify structurally or functionally important amino acid residue sites of β MPs. Furthermore, the TM segments of α ‐helical membrane proteins can be accurately predicted with GeTFEP, suggesting that the GeTFEP is of general applicability in studying membrane protein.